Stability Analysis on Locomotive Radial Bogie - BI XIN; LUO Shi-hui; MA Wei-hua (机车电传动)
In order to understand the relationship between radial mechanisms with critical velocity, radial bogie structure was analyzedand differential equations of wheelset motion were set up. The effect of guide mechanism on wheelset vibration was analyzed in time domainand frequency domain by the dynamic simulation. The results showed that: with radial mechanism coupling the yaw movement of the samebogie end axle wheelsets, asymmetric yaw stiffness could be realized, and in-phase yaw stiffness of wheelset was increased; radial mechanismexcited inverting yaw vibration mode of the bogie and promoted the vibration mode moving to increase damping direction, which couldimprove the stability of the bogie to a certain extent; for the locomotive under the same suspension parameters, the radial mechanism improvedthe nonlinear critical speed by 60%.